Harnessing the value of reproductive hormones in cattle production with considerations to animal welfare and human health. (1st July 2022) - Evans, Holly C; Briggs, Elanie F; Burnett, Randy H; Contreras-Correa, Zully E; Duvic, Morgan A; Dysart, Lacey M; Gilmore, Alicia A; Messman, Riley D; Reid, Dana; Rasit Ugur, Muhammet; Kaya, Abdullah; Memili, Erdogan
Abstract: The human population is ever increasing while the quality and quantity of natural resources used for livestock production decline. This calls for improved product efficiency and the development of improved and sustainable cattle production methods to produce higher quality products to satisfy the demands of both the modern and transient world. The goal of this review was to summarize the interactions, challenges, and opportunities in cattle production relating to their endocrine system, and how reproductive hormones and others impact economically important traits, animal welfare, and human health. A comprehensive literature search was conducted with a focus on analysis of natural hormones and the use of exogenous hormone administration for reproduction, growth, and development of beef and dairy cattle. Hormones regulate homeostasis and enhance important traits in cattle, including fertility, growth and development, health, and the production of both meat and milk products. Reproductive hormones such as testosterone, estradiol, progesterone, and related synthetics like trenbolone acetate and zeranol can be strategically utilized in both beef and dairy cattle production systems to enhance their most valuable traits, but the impact of these substances must account for the welfare of the animal as well as the health of the consumer. This scientific review provides a comprehensive analysis of the bovine endocrine system's impact on food animals and product quality which is vital for students, researchers, livestock producers, and consumers. Although important advances have been made in animal science and related technological fields, major gaps still exist in the knowledge base regarding the influence of hormones on the production and welfare of food animals as well as in the public perception of hormone use in food-producing animals. Filling these gaps through transformative and translational research will enhance both fundamental and applied animal science to feed a growing population. Lay Summary: The animal production industry is responsible for providing products like meat, dairy, and egg products to the growing human population of the world. Within each sector, there are production practices that can improve the overall productivity of the animals and contribute to their welfare. One such avenue for enhanced production is the inclusion of hormones. Hormones are naturally produced within the body by the endocrine system which helps initiate many life processes and transition the body to different stages of production. Hormones influence many important traits such as growth and development, milk production, fertility, and health within the cattle industry. Exogenous hormone use in animals has proven to improve a number of traits and qualities of animal products, but it has also struck up controversy. There are wide deficiencies in the full understanding of roles, applications, and implications of hormones in livestock, making it of high importance for further exploration. In this review, the mechanisms of hormones and their broad uses are explored to provide more context to the conversation of hormone use in animals. Knowledge of endocrinology is powerful and can aid in the advancement of fundamental science and animal development and production. Abstract : The understanding and use of hormones can enhance animal production sectors, particularly that of the cattle industry, in order to create a more productive, sustainable, and animal-centered system.